(untitled) (Journal of the Association for the Study of Australian Literature, 2010)
This paper examines the matter of Ireland in Buckley’s two memoirs, Cutting Green Hay (1983) and Memory Ireland (1985), and the poems of The Pattern (1979), in order to revisit critically the ways in which he constructs himself as a diasporic Irish-Australian, a participant in the most remote Gaeltacht. It raises questions of victimhood, of similar and different experience of being at the mercy of the land, and of his re-engineering of the place of the political in poetry. It argues that Buckley’s agonized positioning as Ireland’s ‘guest/foreigner/son’ was a project that was doomed by its utopianism, and that, obsessed as he became with Ireland, the angst within had little to do with ‘the Ireland within’ or without. The paper suggests that the poet’s slow and unacknowledged abandonment in his Irish period of a key tenet of modernism, its distrust of propaganda and the political, is in itself a new formation which had some continuity with the radicalism of his thinking during the formative years of the revolutionary catholic apostolate he led both at the University of Melbourne and nationally. It also points to the deployment of an ancient medieval Irish trope, that of the ocean (rather than a landmass) linking a dispersed community, as one of the ways the poetry effects a resolution of the issues of being ‘Irish’ in a remote country.